Effect of carburisation process on the wear of steel - Roonie Protasius (2016)
Electro-carburisation process based on liquid carburisation process had been carried out to investigate the effect of the carburization process on the resulting hardness, microstructure change, and the sliding wear resistance of mild steel under dry and lubrication conditions. The carburisation process was conducted in carbonate salts mixtures of Na₂CO₃-NaCI. The electro-carburisation process was first performed and followed by post-carburisation cleaning where subsequent analysis such as hardness test, metallographic observation, EDX/SEM and XRD were then carried out in order to investigate the effect of the carburisation process on the mild steel. Carburisation process resulted in a remarkedable increase in the hardness leading to an enhancement of adhesive and abrasive wear resistance, as well as load carrying capacity. Increasing the duration of the carburisation process from 1 hour to 3 hours resulted in higher peak hardness (727 HV/795 HV), greater case depth (50-100µm/660µm), higher amount of carbide in the grain boundaries and larger retained austenite grains. The surface of the carburised steel was dominated by retained austenite. Towards the core, the amount of retained austenite reduced while the amount of martensite increased. The austenite microstructure in the steel carburised for 1 hour exhibited higher cracking and fracture resistance as compared to the steel carburised for 3 hours. The low cracking and fracture resistance of the steel carburised for 3 hours could be due to its large grain size and high amount of cementite in the grain boundaries as the fatigue strength reduced with an increase in the grain size and the presence cementite could act as fatigue crack initiators. The superior wear resistance of the martensite, as compared to the austenite, could be attributed to its high cracking and adhesive wear resistance owing to its high hardness and tendency to form oxide. The friction was governed by the wear mechanism and the type of microstructure at the worn scar sliding on the carbide ball. It was found that surface fracture and sliding on martensite resulted in higher friction coefficient. The superior wear resistance and load carrying capacity of the carburised steel was also evident under oil lubrication condition. Compared to the austenite, the martensite showed higher tendency to react with the carbon in the oil under extreme boundary lubrication which in turn resulted in a significant drop in the friction coefficient after the running in process.